2018
DOI: 10.1080/23750472.2019.1568906
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the management challenges associated with the implementation of the physically active teaching and learning (PATL) pedagogy: a case study of three Isle of Wight primary schools

Abstract: Enabled partly by government policies by the Department for Culture Media and Sport, some schools are beginning to shift towards promoting a physical activity culture which complements the traditional PE and school sports provision. For many, this entails using physical activity as modality to promote academic performance. Physically Active Teaching and Learning (PATL) is one approach which has been adopted by schools on the Isle of Wight (UK) as part of a holistic island-wide intervention aimed at increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…A recent meta-synthesis (34) shows that relevant theoretical frameworks extending the field include the Socio-Ecological Model (35), the COM-B model (36) and the RE-AIM framework (37). These frameworks map and evaluate teachers' motivation, behaviours and practices using qualitative and quantitative methods such as interviews, focus groups and questionnaires (34,(38)(39)(40)(41).…”
Section: Approaching Physically Active Learning As An Interdisciplina...mentioning
confidence: 99%
“…A recent meta-synthesis (34) shows that relevant theoretical frameworks extending the field include the Socio-Ecological Model (35), the COM-B model (36) and the RE-AIM framework (37). These frameworks map and evaluate teachers' motivation, behaviours and practices using qualitative and quantitative methods such as interviews, focus groups and questionnaires (34,(38)(39)(40)(41).…”
Section: Approaching Physically Active Learning As An Interdisciplina...mentioning
confidence: 99%
“…School children frequently remain sedentary on average between 4 and 5 h per day, and schools are an ideal setting to increase the PA levels of children and reduce sedentary behaviours [45,46]. Traditional approaches to tackling these issues have been aiming to increase the number of PE lessons and providing additional opportunities for extra-curricular sport [47]. Endorsing a whole-school method to PA is a prevalent procedure of government policy, intending to tackle escalating societal trepidations over young people's health.…”
Section: Setting the Pe (And Sport) Landscapementioning
confidence: 99%
“…The fundamental principle of SEM is that behaviour has multiple levels of influence, often involving interactions within the levels of intrapersonal (biological, psychological), interpersonal (interaction within the proximal social network), institutional (the primary organisational network), community (institution beyond the primary institution) and public policy (local, state and national) (Mcleroy et al, 1988). This is a particularly important insight for school-based initiatives, where the behaviour of children, who are still classed as dependants, is directly impacted by influences from school staff and family members (Domville et al, 2018;Mwaanga et al, 2018). A recent rapid realist review, using the five-level socio-ecological model by Mcleroy et al (1988) and Defever and Jones (2021), identified important factors at an intrapersonal (i.e.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The impact of national policy on school-based PA initiatives is complicated and was frequently discussed in the interviews with school staff. Mwaanga et al (2018) argue that the current UK education framework is based on the philosophical view of dualism of the mind and body as a separate entity, and disputably the educational regulatory bodies deem the cognitive function as superior to the physical body function. The academic pressure imposed by the government and the less priority on PA opportunities by school inspectors indeed negatively impact school staff's perceptions on whether school-based PA initiatives are considered worthwhile or not (Domville et al, 2018).…”
Section: Uncovering the Complexity Of External Influencersmentioning
confidence: 99%